Office Hysteroscopy for Infertility: A Series of 557 Consecutive Cases. (14th April 2010) - Koskas, Martin; Mergui, Jean-Luc; Yazbeck, Chadi; Uzan, Serge; Nizard, Jacky
Abstract : Objective . To study incidence of abnormal hysteroscopic findings according to age. Methods . We retrospectively studied 557 consecutive office hysteroscopies in patients referred for incapacity to conceive lasting at least 1 year or prior to in vitro fertilization. Rates of abnormal findings were reviewed according to age. Results . In 219 cases, hysteroscopy showed an abnormality and more than a third of our population had abnormal findings that could be related to infertility. Rates of abnormal findings ranged from 30% at 30 years to more than 60% after 42 years. Risk of abnormal finding was multiplied by a factor of 1.5 every 5 years. Conclusion . Our data are an additional argument to propose office hysteroscopy as part of first-line exams in infertile woman, regardless of age.